2016
DOI: 10.1007/978-3-319-40189-8_27
|View full text |Cite
|
Sign up to set email alerts
|

Parameterized Complexity and Approximation Issues for the Colorful Components Problems

Abstract: The quest for colorful components (connected components where each color is associated with at most one vertex) inside a vertex-colored graph has been widely considered in the last ten years. Here we consider two variants, Minimum Colorful Components (MCC) and Maximum Edges in transitive Closure (MEC), introduced in the context of orthology gene identification in bioinformatics. The input of both MCC and MEC is a vertex-colored graph. MCC asks for the removal of a subset of edges, so that the resulting graph i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Hence, the problems Colourful Partition and Colourful Components are equivalent for trees. The following hardness and FPT results are due to Bruckner et al [3] and Dondi and Sikora [7]. Note that trees of diameter at most 3 are stars and double stars (the graph obtained from two stars by adding an edge between their central vertices), for which both problems are readily seen to be polynomial-time solvable.…”
Section: Known Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…Hence, the problems Colourful Partition and Colourful Components are equivalent for trees. The following hardness and FPT results are due to Bruckner et al [3] and Dondi and Sikora [7]. Note that trees of diameter at most 3 are stars and double stars (the graph obtained from two stars by adding an edge between their central vertices), for which both problems are readily seen to be polynomial-time solvable.…”
Section: Known Resultsmentioning
confidence: 93%
“…A subdivided star is the graph obtained by subdividing the edges of a star. In fact, Dondi and Sikora [7] found a cubic kernel for coloured trees when parameterized by k and also gave an O * (1.554 k )-time exact algorithm for coloured trees. In addition to Theorem 6, Bruckner et al [3] showed that Colourful Components is FPT for general coloured graphs when parameterized by the number of colours ℓ and the number of edge deletions p.…”
Section: Known Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, we show in Section 7 that results similar to those of Section 4, hold also for MEC. A preliminary version of this work appeared in [9].…”
Section: Introductionmentioning
confidence: 99%